Operational signature-based symbolic hierarchical clustering for building energy, operation, and efficiency towards carbon neutrality. (15th February 2023) - Hong, Yejin; Yoon, Sungmin; Choi, Sebin
Abstract: Buildings are considered the enormous source of untapped energy efficiency potential in the global carbon neutrality. It is necessary to ensure that buildings are energy-efficient using operational pattern analytics and diagnostics. Therefore, this study proposes a novel symbolic hierarchical clustering method (named HOS-SAX) to evaluate the building system operation, efficiency, and energy usage patterns. The proposed HOS-SAX method is intended to enhance the existing methods that focus only on the energy usage characteristics and thus offer limited insights on the building system and operational efficiency. The proposed method consists of: (1) Holistic Operational Signature (HOS) and (2) HOS-based symbolic aggregate approximation (SAX) analyses. A HOS analysis is conducted to derive the representative operational signatures for building operation and efficiency using system-, building-, and weather-level data. Then, SAX is performed with the operational signatures derived from the HOS to cluster the building operation patterns. In a case study for a district heating substation serving residential buildings, the HOS-SAX cluster analysis showed 15 sections in the cluster map that visualize the: (1) energy usage, (2) design efficiency, and (3) control efficiency. The cluster map revealed that the sections that operated inefficiently account for approximately 71% of the entire operation period. Moreover, it is expected that the supply temperature of 0.87 °C can be reduced in the most inefficient sections. Highlights: Operational signature-based symbolic aggregation approximation (SAX) method is proposed. Holistic Operational Signatures (HOS) are presented for a district heating substation. Severe inefficient sections derived from the HOS-SAX map accounted for approximately 71%. HOS-SAX cluster analysis can evaluate the building system's operation and efficiency.